SEMIOTIKA IKLAN POLITIK INDONESIA PASCA REFORMASI (Studi Kasus Iklan PPRN, Partai Demokrat, Partai Golkar dan PDIP-Perjuangan) - Sari, Dewi Kartika (KOMUNITAS)
This research was conducted because of the many problems of political advertising in  the  form  of  billboards  that  use  pictures  legislator  candidates  supported  by  the visualization  of  images  the  artist  as  an  endorser  of  political  advertising.  The phenomenon of the use of photographs and photo artists candidate in political ads we encounter in the aftermath of reform. Before thereform era, we see only the logo image and the image of political parties only in billboard advertisements of political parties. The  study,  observed  four billboard  ads  that  use prospective legislators  as endorsernya artist. Roland Barthess semiotic theory is used to analyze political ads is  to  know  the  meaning  of  the  sign  is  coded  and  not coded  in  the  four  studied political  advertising.  Meanwhile,  the  methodology  used  is  descriptive  qualitative research methodology. By using this methodology, expected to know the meaning of the sign system that works on four political ads. Keywords: Semiotics, Meaning, Signs, and Political advertising